Penerapan Metode Pembelajaran Problem Based Introduction (PBI) dalam Meningkatkan Hasil Belajar IPS Pada Siswa Kelas V SD Inpres Dehegila - Subhan Hayun; M. Rais Salim; Jania Hi. Sawawi (Jurnal Ilmiah Wahana Pendidikan, 2021)
The aim of this research is to find out the application of the Problem Based Introduction (PBI) Learning Method in improving Social Studies Learning Outcomes on the types of work for fifth grade students of SD Inpres Dehegila. The type of research used in this research is the Classroom Action Research method known as CAR (Classroom Action Research). This research consists of two cycles and outlines, there are four stages, namely (1) planning, (2) implementation (acting), (3) observation (observing), and (4) reflection (reflecting). Based on data analysis and discussion, the conclusion that can be drawn from this research is that there is an increase in social studies learning outcomes through problem based recognition (PBI) based learning on the types of work. seen when the test was carried out in the first cycle of students who completed 7 or (43.75%) and in the second cycle when the test was carried out increased to 14 or (87.5%). Due to the limited time, the research was not continued to cycle III and only remedial was held until it was completed.